DECISION SUPPORT SYSTEMS INCREASE RANK USING AHP WEB – BASED ON PT TAMBANG BUKIT ASAM (PERSERO) TBK - Wahyuni Fithratul Zalmi (Jurnal Informatika, 2021)
Decision support system is a system adopted from human knowledge, which can help people in the decision making process. In research conducted at PT Coal Bukit Asam (Persero) authors see most of the systems currently used in the search process of promotion of employees still in manual form, causing the length of the assessment process associated with a promotion for every employee of the company in accordance with any the criteria that have been specified company. Various weighting of criteria and sub criteria established companies are always considered manager to each process of inputting assessment. Therefore, the authors make a decision support system application manager that can facilitate the process of inputting weight rating decision promotion of employees in accordance with the criteria and sub-criteria that have been specified company. Application decision support system of promotion is designed using Analytical Hierarchy Process that the process to obtain the priority weighting is done by comparing each criteria and sub-criteria. Decision to be achieved can help managers to determine who the employees are entitled to a promotion in accordance with keptusan obtained from the application of this decision-making system.